From poverty reduction to mutual interests? The debate on differentiation in EU development policy - Svea Koch (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This paper looks into the issue of how European Union (EU) development policy can respond to a changing development landscape that is characterised by a different geography of power and wealth and a changing geography of global poverty. The question of how to differentiate its partnerships and how to best engage with middle-income countries (MICs) has been among the most discussed issues in the ongoing process of modernising EU development policy. The analysis in this paper puts the question of aid to MICs in the context of two interlinked challenges: (i) the need to reconceptualise dominant approaches to global poverty reduction that prioritise national income as a key guiding criterion to classify countries, and (ii) the growing range of global challenges that require development policy to diversify its objectives. With regards to the implications for EU development policy, the paper draws two main conclusions. First, tackling global poverty needs a better coordinated cross-country division of labour at the EU level to avoid marginalising countries that have become wealthier in per capita terms but that continue to experience internal development challenges. Second, addressing challenges related to complex global public goods requires EU development policy to continue its engagement with emerging economies and other increasingly powerful developing countries. Such diversification of objectives, however, will increase the coordination challenges of EU development policy and other European external policies substantially.
Keywords: 330